ASSESSMENT OF STATE-OWNED BANK HEALTH LEVEL USING THE RGEC METHOD DURING THE COVID-19 PANDEMIC - Ana Dwi Pertiwi (Asosiasi Dosen Muda Indonesia, 2022)
In March of 2020, the Covid-19 virus reached Indonesia. Almost every industrial sector in Indonesia has been negatively affected including banking industry. This study aims to analyze how the health level of state-owned banks during the Covid-19 pandemic is using the RGEC method. The data used in this study is the annual report of state-owned bank for the 2020-2021 period. Sample in this study is state owned bank. The data analysis technique used in this research is by analyzing financial statements using the RGEC method. The result of this study shows that in 2020 and 2021 Bank Rakyat Indonesia (Persero) Tbk and Bank Mandiri (Persero) Tbk received a Very Healthy rating. Bank Tabungan Negara (Persero) received a Healthy rating in 2020 and 2021. Bank Negara Indonesia (Persero) Tbk received a Fairly Healthy rating in 2020, and in 2021 it received a Healthy rating.